Peranan Integritas Gembala terhadap Pertumbuhan Rohani Jemaat GPDI Kasih Karunia Tebing Tahun 2025 - Alfred Arswendo Marpaung; Lisbet Parulian Simangunsong; Tirsanika Surbakti; Herlina S. Sinaga; Kogilambal Kogilambal (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The role of pastoral integrity in fostering the spiritual growth of the congregation at GPdI Kasih Karunia Tebing Tinggi is an important subject of study. This research aims to: (1) determine the level of pastoral integrity at GPdI Kasih Karunia Tebing Tinggi; (2) identify the condition of the congregation's spiritual growth; and (3) analyze and empirically examine the influence of pastoral integrity on the spiritual growth of the congregation at GPdI Kasih Karunia Tebing Tinggi. This study employed a quantitative research method by distributing questionnaires to church members to collect data. Since the sample size consisted of fewer than 50 respondents, the Shapiro–Wilk test was used to assess data normality. The results of the Shapiro–Wilk residual test indicated a significance value of 0.177 for Variable X and 0.386 for Variable Y. As both significance values exceeded 0.05, the data were considered to be normally distributed. The findings revealed that pastoral integrity has a significant positive influence on the spiritual growth of the congregation by providing exemplary leadership and fostering trust within the church community. The study confirmed a significant relationship between pastoral integrity (X) and the spiritual growth of the congregation at GPdI Kasih Karunia Tebing Tinggi (Y), with a correlation coefficient (R) of 0.627 and a coefficient of determination (R²) of 39.4%. This indicates that pastoral integrity accounts for 39.4% of the variance in the congregation's spiritual growth, while the remaining 60.6% is explained by other variables beyond the scope of this research model.